Reinventing residual reserves in the sea: are we favouring ease of establishment over need for protection?. Issue 4 (25th February 2014) - Devillers, Rodolphe; Pressey, Robert L.; Grech, Alana; Kittinger, John N.; Edgar, Graham J.; Ward, Trevor; Watson, Reg
Abstract As systems of marine protected areas (MPAs) expand globally, there is a risk that new MPAs will be biased toward places that are remote or unpromising for extractive activities, and hence follow the trend of terrestrial protected areas in being 'residual' to commercial uses. Such locations typically provide little protection to the species and ecosystems that are most exposed to threatening processes. There are strong political motivations to establish residual reserves that minimize costs and conflicts with users of natural resources. These motivations will likely remain in place as long as success continues to be measured in terms of area (km2) protected. The global pattern of MPAs was reviewed and appears to be residual, supported by a rapid growth of large, remote MPAs. The extent to which MPAs in Australia are residual nationally and also regionally within the Great Barrier Reef (GBR) Marine Park was also examined. Nationally, the recently announced Australian Commonwealth marine reserves were found to be strongly residual, making almost no difference to 'business as usual' for most ocean uses. Underlying this result was the imperative to minimize costs, but without the spatial constraints of explicit quantitative objectives for representing bioregions or the range of ecological features in highly protected zones. In contrast, the 2004 rezoning of the GBR was exemplary, and the potential for residual protection was limited by applying a systematic set of planning principles, such as representing a minimum percentage of finely subdivided bioregions. Nonetheless, even at this scale, protection was uneven between bioregions. Within‐bioregion heterogeneity might have led to no‐take zones being established in areas unsuitable for trawling with a risk that species assemblages differ between areas protected and areas left available for trawling. A simple four‐step framework of questions for planners and policy makers is proposed to help reverse the emerging residual tendency of MPAs and maximize their effectiveness for conservation. This involves checks on the least‐cost approach to establishing MPAs in order to avoid perverse outcomes. © 2014 The Authors. Aquatic Conservation: Marine and Freshwater Ecosystems published by John Wiley & Sons, Ltd.